Thin-film electronics based on all-2D van der Waals heterostructures. Issue 4 (2nd October 2021) - Liu, Xinling; Yang, Xiaomin; Sang, Weihui; Huang, Hai; Li, Wenwu; Lin, Yen-Fu; Chu, Junhao
Abstract : Two-dimensional (2D) layered materials including metal, semiconductor, and insulator have received extensive attention in recent years. The weak van-der-Waals (vdW) interactions between 2D materials layers enable them to isolate monolayers and restack into artificial 2D vdW heterostructures in the desired sequence. These assembled all-2D vdW heterostructures are promising platforms for fabricating next-generation electronics as well as optoelectronics. In particular, the all-2D vdW heterostructure devices composed entirely of 2D layered material have received extensive attention due to their natural thickness, atomically sharp heterointerfaces, and excellent mechanical flexibility. Herein, we firstly introduce 2D vdW heterostructures and their preparation methods. Secondly, the recent progress of field-effect transistors (FETs) and photodetectors based on all-2D vdW heterostructures are summarized. Finally, we discuss some challenges of all-2D vdW heterostructure-based devices for practical applications and offer personal perspectives toward the future development of thin-film electronics.